(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The job satisfaction is known as attitude of an individual towards hisher job. The Jobsatisfaction is related to one‟s personal adjustment in teaching students in the class as per theirintelligent quotient. The Job stress is a negative factor affecting the teaching ability of a teacherirrespective of his personality. The aim of the present research was to find out the job stress and jobsatisfaction among male teachers working in different types of schools of U.P. For that purpose, twohundred and forty male teachers (N = 240) were selected as a sample from total 60 schools (government,missionary and madrasa) of U.P. with age ranged from 25 to 32 years. Job satisfaction scale of Dr. (Mrs.)Meera Dixit, and Indore teachers Job stressors scale of Dr. (Mrs.) Meena Buddhisagar Rathod and Dr.Madhulika Verma were used as instruments for the study. The finding of the study revealed that nosignificant difference was found in mean scores of job stress and job satisfaction among male teachersof government, missionary and Madrasa School. It was concluded that male government school teacherswere significantly better in terms of overall Job Satisfaction than other Schools of U.P.